Comparison of Visual and Refractive Outcomes Between Refractive Lens Exchange and Keratorefractive Lenticule Extraction Surgery in Moderate to High Myopia - Chia-Yi Lee; Shun-Fa Yang; Hung-Chi Chen; Ie-Bin Lian; Jing-Yang Huang; Chao-Kai Chang (Diagnostics)
Background/Objectives: To evaluate the visual and refractive outcomes of keratorefractive lenticule extraction (KLEx) surgery and refractive lens exchange (RLE) surgery in moderate to high myopia patients. Methods: A retrospective cohort study was performed, and patients receiving KLEx or RLE surgeries with myopia within −3.00 to −10.00 diopter (D) were enrolled. A total of 19 and 35 patients were put into the RLE and KLEx groups after exclusion. The main outcomes are postoperative uncorrected visual acuity (UDVA), the spherical equivalent (SE), and residual astigmatism via vector analysis. Fisher’s exact test and the Mann–Whitney U test were utilized for the statistical analysis. Results: The percentages of patients who reached UDVA results of more than 20/25 and 20/20 were statistically similar between groups (both p > 0.05), and the percentages of patients who reached SE results within ±0.50 D and ±1.00 D were statistically similar between groups (both p > 0.05). The change in SE in the KLEx group was lesser compared to that in the RLE group (p = 0.021). The vector analysis showed a lower DV and ME and a higher CoI in the KLEx group than in the RLE group (all p < 0.05). The percentage of patients who reached specific UDVA and SE thresholds were statistically similar between groups with different myopia degrees (all p > 0.05). Conclusions: The postoperative visual and refractive outcomes between RLE and KLEx surgeries are grossly comparable, while the KLEx may have a slight advantage in astigmatism correction.